# How can the logical equivalence for proof by contradiction be represented without $\bot$?

Proof by contradiction (general): assume $$\lnot P$$ and derive a contradiction. This corresponds, in the framework of propositional logic, to the equivalence

$${\text{p}}\equiv {\text{p}}\vee \bot \equiv \lnot \left(\lnot {\text{p}}\right)\vee \bot \equiv \lnot {\text{p}}\to \bot },$$ where $$\bot$$ is a logical contradiction or a false statement (a statement which truth value is false).

In the case where the statement to be proven is an implication $$A\rightarrow B}$$, ...:

Proof by contradiction: assume $$A$$ and $$\lnot B}$$ and derive a contradiction. This corresponds to the equivalences

$${\text{p}}\to {\text{q}}\equiv \lnot {\text{p}}\vee {\text{q}}\equiv \lnot \left({\text{p}}\wedge \lnot {\text{q}}\right)\equiv \lnot \left({\text{p}}\wedge \lnot {\text{q}}\right)\vee \bot \equiv \left({\text{p}}\wedge \lnot {\text{q}}\right)\to \bot }.$$

In some mathematical logic books, e.g. Ebbinghaus' Mathematical Logic, $$\bot$$ is not defined. How can the two logical equivalence instances for proof by contradiction be represented?

Thanks.

• If satisfied by one of the answer below, please accept it Sep 9, 2020 at 14:19

When $$\bot$$ is not defined, then a contradiction is just that … some statement and its negation.

So, we just do likewise. Either derive $$p\equiv\neg p\to(q\wedge\neg q)$$ or... \begin{align}p &\equiv p\vee( q\wedge\neg q)\\&\equiv (p\vee q)\wedge(p\vee\neg q)\\&\equiv (\neg\neg p\vee q)\wedge(\neg\neg p\vee\neg q)\\&\equiv (\neg p\to q)\wedge(\neg p\to\neg q)\end{align}

In Ebbinghaus' system we have a contradiction in a proof when a pair of formulas: $$ψ,¬ψ$$ is derivable (see page 61).

Using the derived rule for conjunction (Ex.3.6. (b), page 65), from a contradictory pair we can derive the "usual" contradiction: $$ψ ∧ ¬ψ$$.

Ebbinghaus' system has no $$\bot$$ symbol and thus the Contradiction Rule (2.4, page 63) is expressed through two sequents deriving a contradictory pair of formulas.

Having said that, there are not two different "forms" of proof by contradiction.

The first one described in your post amounts to:

$$\dfrac {\Gamma \ \lnot \varphi \vdash \bot}{\Gamma \ \ \ \ \ \vdash \varphi}$$,

which is Ebbinghaus' Contradiction Rule written using $$\bot$$ symbol.

The second one is exactly the same:

$$\dfrac {\Gamma \ \varphi \ \lnot \psi \vdash \bot}{\Gamma \ \varphi \ \ \ \ \ \ \vdash \psi}$$.

Nothing has changed. We can use the so-called Deduction Theorem (aka: Conditional Proof rule, Ex.3.6. (c), page 66) to conclude with:

$$\Gamma \vdash \varphi \to \psi$$.

The result exploits the equivalence between the two formulas: $$\lnot (\varphi \land \lnot \psi)$$ and $$(\varphi \to \psi)$$.